1999
DOI: 10.1002/(sici)1521-3773(19990201)38:3<351::aid-anie351>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Amination of Propanediols in Supercritical Ammonia

Abstract: Enhancements in selectivity by a factor of 4 to 18 were observed in the near critical regions of ammonia during the Co- and Ni-catalyzed synthesis of 1,3-diaminopropanes. These results are attributed to the higher concentration of ammonia at the surface of the catalyst, which favors the amination and suppresses degredation reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…High reaction pressure is known to be crucial to improve the selectivity of primary diamines due to the formation of supercritical ammonia (critical data of ammonia: T c = 132.4 °C, P c = 11.48 MPa) during reaction. 14,59,60 In our subsequent pilot-scale study (entry 5, Table 2), 50.4% conversion with a selectivity of 82.1% for EDA was achieved at 175 °C under 17. 3.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 92%
“…High reaction pressure is known to be crucial to improve the selectivity of primary diamines due to the formation of supercritical ammonia (critical data of ammonia: T c = 132.4 °C, P c = 11.48 MPa) during reaction. 14,59,60 In our subsequent pilot-scale study (entry 5, Table 2), 50.4% conversion with a selectivity of 82.1% for EDA was achieved at 175 °C under 17. 3.…”
Section: Experimental and Theoretical Methodsmentioning
confidence: 92%
“…Fischer et al have reported that ammonia would form a supercritical uid (critical data of ammonia: T c ¼ 132.4 C, P c ¼ 11.48 MPa) in a x-bed reactor under high pressure. 9,10 The formation of supercritical ammonia is crucial to improve the selectivity of primary diamines. Unfortunately, our reaction pressure should not exceed 8 MPa due to the limitations of experimental conditions.…”
Section: Reductive Amination Of Meamentioning
confidence: 99%
“…[1][2][3][4] The reductive amination method has gained increasing interest since it constitutes a green economy route for the synthesis of ethylene amines. [5][6][7][8][9][10][11][12][13][14] In the reductive amination process, ethylene amines are synthesized by contacting MEA and ammonia under hydrogen atmosphere in the presence of hydrogenation-dehydrogenation metal catalysts. The reaction pathways for the transformation of MEA to ethylene amines on a metal catalyst are postulated as follows: rstly, dehydrogenation of MEA to 2-aminoacetaldehyde; secondly, condensation with ammonia or an amine to form imine; lastly, hydrogenation of imine to amine.…”
Section: Introductionmentioning
confidence: 99%
“…Aliphatic primary amines can be synthesized by the reductive amination of the corresponding carbonyl compounds with NH 3 , 49 but selective synthesis of primary amines is challenging due to their high reactivity. Although heterogeneous catalysts are used for reductive amination of simple alcohols under H 2 , 50 they suffer from drawbacks such as a limited substrate scope, low selectivity for primary amines and the need of a high temperature (>200 °C), high H 2 pressure, and high pressure of NH 3 (supercritical NH 3 ). Mizuno et al developed heterogeneous Ru 39b and Cu 44e catalysts for multialkylation of aqueous ammonia (or urea) by alcohols to secondary and tertiary amines.…”
Section: N-alkylation Of Nh 3 or Urea With Alcoholsmentioning
confidence: 99%